2001
DOI: 10.1006/jmla.2000.2762
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic Boundaries in Adjunct Attachment

Abstract: Five studies explored the processing of ambiguous sentences like Martin maintained that the CEO lied when the investigation started/at the start of the investigation. The central question was why particular prosodic boundaries have the effects they do. A written questionnaire provided baseline preferences and suggested that clausal adjuncts (when the investigation started) receive more high attachments than nonclausal adjuncts (at the start of the investigation). Four auditory studies manipulated the prosodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
155
5
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(172 citation statements)
references
References 24 publications
9
155
5
3
Order By: Relevance
“…It has been suggested that prosodic representations are computed as an utterance is processed, and that such representations contribute to processes such as the assignment of syntactic structure (e.g. Carlson, Clifton, & Frazier, 2001;Kjelgaard & Speer, 1999). If a prosodic structure has to be computed to contribute to establishing the syntactic structure of an utterance, it can also be used to modulate lexical activation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that prosodic representations are computed as an utterance is processed, and that such representations contribute to processes such as the assignment of syntactic structure (e.g. Carlson, Clifton, & Frazier, 2001;Kjelgaard & Speer, 1999). If a prosodic structure has to be computed to contribute to establishing the syntactic structure of an utterance, it can also be used to modulate lexical activation.…”
Section: Discussionmentioning
confidence: 99%
“…Listeners may marshall all of this evidence for prosodic structure as they process continuous speech. It has been argued, e.g., that prosody is used by listeners to help retrieve the syntactic structure of utterances (e.g., Schafer, 1997;Kjelgaard & Speer, 1999;Carlson, Clifton, & Frazier, 2001;Jun, 2003) and to help in word recognition (e.g., Kim, 2003Kim, , 2004a. Information specifying the location of prosodic boundaries may also be used by listeners to help resolve lexical ambiguities in the segmentation of continuous speech (Salverda, Dahan, & McQueen, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Manipulations of prosodic structure influence how listeners interpret syntactically ambiguous utterances (Lehiste 1973;Lehiste, Olive & Streeter 1976;Beach, 1991;Cooper & Paccia-Cooper 1980;Price, Ostendorf, Shattuck-Hufnagel, & Fong, 1991;Schafer, 1997;Carlson, Clifton & Frazier, 2001; see Cutler, Dahan & van Donselaar, 1997 for a review). These effects of prosody emerge quickly during online sentence comprehension, suggesting that this is a robust property of the human parser (Marslen-Wilson, Tyler, Warren, Grenier, & Lee, 1992;Nagel, Shapiro, Tuller, & Nawy, 1996;Pynte & Prieur, 1996;Kjelgaard & Speer, 1999;Steinhauer, Alter & Frederici, 1999;Snedeker & Trueswell, 2003;Warren, Grabe & Nolan, 1995;Weber, Grice & Crocker, 2006).…”
Section: Authors' Notementioning
confidence: 99%
“…Other theories focus on a more limited range of phenomena and characterize the mapping within this domain. One commonly explored phenomenon is the prosodic phrasing of syntactic attachment ambiguities (Schafer, 1997;Carlson et al, 2001;Clifton, Carlson & Frazier, 2002). There are several reasons why this might be a particularly productive place to begin pinning down the syntax-prosody interface.…”
Section: Authors' Notementioning
confidence: 99%